Dharma Lion : A Biography of Allen Ginsberg - Schumacher, Michael, 1950- (Book collections on Project MUSE., 2016)
With the sweep of an epic novel, Michael Schumacher tells the story of Allen Ginsberg and his times, with fascinating depictions of Jack Kerouac, Neal Cassady, and William Burroughs, among others, along with many rarely seen photographs.